Below the radar: the boom of groundwater use in the central part of the Nile Delta in Egypt - El-Agha, Doaa E.; Closas, Alvar; Molle, Francois (Springer, 2017)
The Nile Delta of Egypt is known for its large irrigated area supplied with water diverted from the Nile River, with a limited use of groundwater, largely for domestic and industrial use. Official statistics for the whole delta indicate that there are a few thousand individual wells used for agriculture by a population of over 2 million farmers. This study, however, shows that a phenomenon of groundwater development for irrigation has been unfolding over the last few years, largely below the radar of managers and researchers. A survey was carried out in the central part of the delta with the objective of (1) uncovering the actual situation of groundwater use in this part of the delta and (2) speculating on its implications. The results of the survey pointed to a recent and booming tube-well drilling industry, with well densities in some parts reaching one well every 2 ha. The development of groundwater abstraction in the central delta is strongly linked to inadequate and/or untimely availability of surface water in the canals. A technical, economic, and management characterization of wells complements the study, showing a continuum between purely private/individual ownership of wells and collective investments and management. Lastly, the article explores the implications of unchecked abstraction at the farm, local and delta scales.